(untitled) (Research, Society and Development, 2022)
The Brazilian Magna Carta properly expresses unequivocally that education is a duty of the state and a right of the Brazilian citizen. This research measures the annual efficiency of Federation Units and the variation in total factor productivity, comparing public resources by the state secondary education network and the results of the Basic Education Development Index from 2013 to 2019. Descriptive, exploratory, quantitative research and using secondary data. Use Data Envelopment Analysis to measure annual efficiency and Malmquist’s(1953) Total Factor Productivity Index to assess productivity in the period. The results induced that 74% of the observed Federation Units are inefficient. However, there was an average productivity gain of 2%. The results obtained that the improvement is more a matter of unexplored production capacity than scarcity of resources, having difficulties in the incorporation of new technologies. This study contributes to the expansion of the debate on the efficiency of public spending and to the instrumentalization of social control by public managers over approvals for the delivery of a learning process capable of reducing socioeconomic inequalities and building a more participatory and critical society.